Anaerobic treatment of abattoir waste: Biogas production and correlation parameter in a batch reactor system. (October 2020) - Odekanle, E.L.; Dahunsi, S.O; Zahedi, S.
Highlights: The possibility of energy generation from abattoir wastes was evaluated. Results shows that abattoir waste is rich in minerals and elemental compositions. A cumulative biogas volume of 8.37 l was obtained from a 25 l digester volume. A lower heating value LHV of 20, 400 kJ/m 3 was obtained from the biogas. Abstract: In developing countries, the continuous need to increase meat production for the growing population has resulted in upsurge in the number of abattoirs or slaughterhouses within their major cities. Most of these abattoirs release huge amount of wastewater to the environment with little or no concern for resultant health effects. In this study, anaerobic digestion for biological treatment of abattoir waste in a batch reactor system was investigated. Correlation parameters that relate average gas production rate and working volume of digester were also developed. Abattoir wastewater was anaerobically digested for 30 d. During the period, the pH, temperature, chemical oxygen demand (COD), total solid (TS), and total volatile solid (TVS) were determined every 24 h. In 30 d, 30.9 L of biogas was produced with average daily yield of 1.03 L. A total of 84.1% of COD, 83% of TVS and 77% of TS were removed after the digestion period. These parameters were used to develop correlations between the average gas production rate and working volume of digester based on reduced COD, TVS and TS; and this was found to be in good agreement with the obtained experimental results.